Professionalism in science - Ramsden, Jeremy J. (Collegium Basilea & AMSI, 2009)
In everyday speech, the word “professional” has an ambiguous ring, applied to one who follows, by way of profession, what is ordinarily regarded as a pastime (e.g., a sport), or disparagingly applied to one who “makes a trade” of politics and the like. In this sense it is contrasted with “amateur”, one who does something, literally, for the love of it, without remuneration. The latter is generally regarded as superior to the former; remuneration being considered as likely to irremeably invest the activity with self-interest, resulting in the task at hand being merely accomplished with the minimally sufficient expertise and skill to obtain the offered remuneration, whereas the amateur strives to do whatever task is at hand as well as he or she possibly can, “ excellence for its own sake”.